Plasma etching of SiO2 using heptafluoropropyl methyl ether and perfluoropropyl vinyl ether - Kim, Jun Hyun; Park, Jin Su; Kim, Chang Koo (ECS Journal of Solid State Science and Technology, 2018)
As alternative to perfluorocompounds, hydrofluoroether and perfluoroalkyl vinyl ether were used for SiO2 etching. SiO2 was etched in heptafluoropropyl methyl ether (HFE-347mcc3)/Ar and perfluoropropyl vinyl ether (PPVE)/Ar plasmas, separately, and their etch characteristics were compared at bias voltages ranging from −400 to −1200 V. The etch rate of SiO2 in a HFE-347mcc3/Ar plasma was approximately 2.5 times higher than that in a PPVE/Ar plasma at a bias voltage of −400 V. However, the difference in the etch rates decreased with increasing bias voltage, reaching nearly zero at a high bias voltage of −1200 V. The change in the etch rate of SiO2 was attributed to not only the amount of F radicals but also the characteristics in the steady-state fluorocarbon films formed on the SiO2 substrate. In the low-bias voltage regime (−400 to −800 V), higher etch rates in a HFE-347mcc3/Ar plasma than those in a PPVE/Ar plasma were obtained because both the thickness and fluorine-to-carbon (F/C) ratio of the steady-state fluorocarbon film controlled the etch rate of SiO2. On the other hand, the F/C ratio of the steady-state fluorocarbon film, rather than its thickness, limited the etch rate of SiO2 in the high-bias voltage regime (−800 to −1200 V).
Keywords: Etch rates; Fluorocarbon films; Hydrofluoroether; Low bias voltage; Methyl ethers; Perfluorocompounds; Steady state; Vinyl ethers